(untitled) (Medicine Today, 2023)
Introduction: Laparoscopic cholecystectomy has been performed for decades and is a fairly standardized procedure throughout the world. Occlusion of the cystic duct is popularly done with the help of metal clips. There are many other techniques described in the literature to deal with occlusion of the Cystic Duct. Suture ligation of the duct is one such way.To evaluate the effectiveness in term of cost, safety, and complication in occlusion of cystic duct with suture ligation compared to clip application. Materials and Methods: A prospective cross sectional comparative study was carried out From June 2020 to November 2020. Data were collected from 80 patients undergone laparoscopic cholecystectomy for Gall stone diseases. 40 patients were enrolled in each group by consecutive purposive sampling. Complete history was taken. Thorough clinical examination was done. Relevant investigations report was collected. Results: Female patients were predominant in both groups and most of the patients were underweight. Mean time for ligation was more in occlusion of cystic duct with clip application. Bile leakage was found and duration of drain in situ was more in occlusion with clip application. Cost was high in occlusion with clip application. Conclusion: : Time for ligation, Bile leakage, mean duration of drain in situ (days), and cost of Cystic Duct occlusion and port closure were significantly higher in Laparoscopic Cholecystectomy with conventional Clip application of Cystic Duct group in comparison to Laparoscopic Cholecystectomy with ligation of the Cystic duct with no-1vicryl by extra corporeal knotting group. Medicine Today 2023 Vol.35(1): 27-30